Oriental Building seen from the Manufactures Building entrance, Alaska-Yukon-Pacific Exposition, Seattle, Washington, 1909 - Nowell, Frank H., 1864-1950 (1909)
Caption on image: Oriental Foreign Exhibit Building and Entrance to Manufacturers' Building, Alaska-Yukon-Pacific Exposition, Seattle, Wash. 1909 Publisher: Portland Post Card Co. Printed on verso: No. X149 PH Coll 78.105 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number